The lentiginoses: cutaneous markers of systemic disease and a window to new aspects of tumourigenesis. Issue 11 (15th June 2005) - Bauer, A J; Stratakis, C A
Abstract : Familial lentiginosis syndromes cover a wide phenotypic spectrum ranging from a benign inherited predisposition to develop cutaneous lentigines unassociated with systemic disease, to associations with several syndromes carrying increased risk of formation of hamartomas, hyperplasias, and other neoplasms. The molecular pathways involved in the aetiology of these syndromes have recently been more clearly defined and several major cellular signalling pathways are probably involved: the protein kinase A (PKA) pathway in Carney complex (CNC), the Ras/Erk MAP kinase pathway in LEOPARD/Noonan syndromes, and the mammalian target of rapamycin pathway (mTOR) in Peutz-Jeghers syndrome and the diseases caused by PTEN mutations. Here we discuss the clinical presentation of these disorders and discuss the molecular mechanisms involved. The presence of lentigines in these diseases caused by diverse molecular defects is probably more than an associated clinical feature and likely reflects cross talk and convergence of signalling pathways of central importance to embryogenesis, neural crest differentiation, and end-organ growth and function of a broad range of tissues including those of the endocrine, reproductive, gastrointestinal, cardiac, and integument systems.